Ajaran Resiliensi dalam Al-Qur’an Surat Yusuf untuk Menghadapi Pandemi Covid-19 - Hasan, Moh. Abdul Kholiq (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
The Teaching of Resilience in the Al-Qur’an Surah Yusuf to Face the Covid-19 Pandemic This research aims to investigate the teaching of resilience in Surah Yusuf and its implementation for Indonesia amidst the COVID-19 pandemic. This study employs library research method with qualitative descriptive approach. Content analysis theory was used to analyse the text of Surah Yusuf and relevant commentaries, while the positive psychology approach is used for the implementation of resilience teachings to individuals and society. The results indicate that the concept of resilience in Surah Yusuf is generally built on three main factors including piety (I have), patience (I am), and iá¸¥sÄn (I can). The aspects of resilience in Surah Yusuf which can be implemented amidst the COVID-19 pandemic in Indonesia are patience, gratitude, resignation, optimism, innovation, solution, self-confidence, reputation, empathy, forgiveness, trust, professionalism, and prayer. In the resilience teaching in Surah Yusuf, the role of spiritual values in the process of building resilience is more decisive, when compared to western model resilience. The higher the individual’s spiritual value, the stronger the level of resilience